2012
DOI: 10.1590/s0365-05962012000600010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological challenge in the differential diagnosis of diffuse alopecia: female androgenetic alopecia, telogen effluvium and alopecia areata - part II

Abstract: Diffuse alopecia is mainly caused by telogen effluvium, diffuse androgenetic alopecia (female-pattern hair loss) and diffuse alopecia areata. Differential diagnosis between the three disorders may be difficult in several occasions. In this second part of our study, chronic telogen effluvium and diffuse alopecia areata are discussed in detail, including clinical, dermoscopic and histological aspects. A flowchart presents a practical and objective differential diagnostic approach to diffuse alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 29 publications
2
52
0
7
Order By: Relevance
“…Onset is usually sudden and progression fluctuates but is self-limiting; in addition it often presents as a bitemporal regression of the hairline. 49,50 It has been suggested that the process is due to a decreased duration of the anagen phase, thereby impeding the growth of long hairs. 45,51 Biopsy reveals a scalp that hardly differs, if at all, from a normal scalp, with a slight increase in the percentage of follicles in telogen if the biopsy is performed during the most active phases.…”
Section: Telogen Effluviummentioning
confidence: 99%
“…Onset is usually sudden and progression fluctuates but is self-limiting; in addition it often presents as a bitemporal regression of the hairline. 49,50 It has been suggested that the process is due to a decreased duration of the anagen phase, thereby impeding the growth of long hairs. 45,51 Biopsy reveals a scalp that hardly differs, if at all, from a normal scalp, with a slight increase in the percentage of follicles in telogen if the biopsy is performed during the most active phases.…”
Section: Telogen Effluviummentioning
confidence: 99%
“…Common triggers include stress, hormonal fluctuations, medications, iron deficiency, trauma, and insufficient protein intake (Werner & Mulinari-Brenner, 2012). Common triggers include stress, hormonal fluctuations, medications, iron deficiency, trauma, and insufficient protein intake (Werner & Mulinari-Brenner, 2012).…”
Section: Telogen Effluviummentioning
confidence: 99%
“…Moreover, it is not uncommon for telogen effluvium to be superimposed on other forms of alopecia if patients experience an inciting event. Important differential diagnoses to consider include androgenetic alopecia (AGA), female pattern hair loss (FPHL), and diffuse AA (35, 36). Acute telogen effluvium occurs 3–4 months after an inciting event, lasts approximately 3 months, and spontaneously resolves, while chronic telogen effluvium usually lasts longer than 6 months.…”
Section: Hair Cycle Disturbancesmentioning
confidence: 99%